PENATALAKSANAAN PASIEN CEMAS PADA PENCABUTAN GIGI ANAK DENGAN MENGGUNAKAN ANESTESI TOPIKAL DAN INJEKSI - Wasilah, Wasilah; Probosari, Niken (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
In dental care, tooth extraction without injection (topical anesthetic), extraction with injection (anesthetic injection), and drilling are condition triggering anxiety of patients. Difficulty in dental treatment for children can be overcome by understanding psychological aspect of children in a certain age. Some principles in handling children are good psychological approach, effective management technique of patient, empathy, and supporting circumstances. Thus, it is advisable to consider some techniques which are successfully-proved in psychology and may be applied in dental care such as attitude development, Tell-Show-Do, desensitization, reinforcement, modeling and sedation.